Changes in corneal parameters at confocal microscopy in treated glaucoma patients - Ranno S (Dove Medical Press, 2011)
Stefano Ranno1, Paolo Fogagnolo2, Luca Rossetti3, Nicola Orzalesi3, Paolo Nucci11Eye Clinic, San Giuseppe Hospital, University of Milan, Milan, Italy; 2GB Bietti Foundation for Study and Research in Ophthalmology, Rome, Italy; 3Eye Clinic, Department of Medicine, San Paolo Hospital, University of Milan, Milan, ItalyBackground: The purpose of this study was to evaluate corneal parameters in treated glaucoma patients, nontreated glaucoma patients, and normal subjects using confocal microscopy.Methods: Forty patients with primary open-angle glaucoma and 22 untreated controls underwent confocal microscopy of the cornea using the Heidelberg retinal tomograph cornea module. The glaucoma group was divided into two subgroups, ie, patients on medical treatment for at least two years before inclusion (with beta-blockers or prostaglandin analogs) and nontreated glaucoma patients. The following corneal parameters were evaluated: endothelial cell density and number, reflectivity, and tortuosity of sub-basal nerves. For reflectivity and tortuosity, a dedicated grading scale ranging from 0 to 4 was used. Differences between treatments were also evaluated in the treated glaucoma group.Results: Number of fibers and reflectivity of the sub-basal plexus were significantly lower in glaucoma patients as compared with controls (2.5 ± 0.7 versus 2.9 ± 0.9, P = 0.006, and 2.3 ± 0.8 versus 2.7 ± 0.9, P = 0.04, respectively), whereas tortuosity was significantly higher (2.6 ± 1 versus 2.0 ± 0.8, P = 0.007). Endothelial cell density (measured as cells per mm2) was lower in the glaucoma group comparing treated patients with nontreated patients (2826 ± 285 versus 3124 ± 272, P = 0.0003). Comparing treated patients with nontreated patients, relevant differences were found in number (2.3 ± 0.7 versus 2.8 ± 0.8, P = 0.004), tortuosity (2.8 ± 1 versus 2.2 ± 0.8, P = 0.004), and reflectivity (2.2 ± 0.8 versus 2.6 ± 0.8, P = 0.04). No differences in corneal parameters were found between beta-blockers and prostaglandin analogs.Conclusion: This study shows that differences in corneal parameters between glaucoma patients and controls may be due to the medical treatments used for glaucoma. These data should be taken into consideration in long-standing medical glaucoma treatment and in potential candidates for surgery.Keywords: cornea, glaucoma, sub-basal nerves, endothelial cells, confocal microscopy